Developing a tool to evaluate early childhood education implementation fidelity: Measure of Montessori Implementation pilot study results - Murray, Angela K.; Murray, Amelia J.; Daoust, Carolyn J.; Gerker, Heather E. (Frontiers in Education, 2025)
IntroductionThe Measure of Montessori Implementation-Early Childhood (MMI-EC) is a first of its kind classroom observation instrument designed to support research in Montessori classrooms. Fidelity measurement is an important aspect of quality educational research and evaluation and is even more important for research on Montessori education because the name is not legally protected. Any school can claim to be Montessori regardless of their practices. In the absence of a tool like the MMI-EC, researchers have utilized a variety of proxies to gauge Montessori fidelity with a wide range of rigor.MethodsThe MMI-EC involves a 45-min live classroom observation period conducted while children engage in learning activities as well as a separate documentation of classroom characteristics and equipment. The live observation consists of 5-min time samples of teacher activity and the materials students are engaged with. The classroom characteristics include both Montessori learning materials as well as other features supportive of high-quality Montessori implementation. We present results from a pilot study of 81 classroom observations using the MMI-EC conducted in both public and private Montessori early childhood classrooms in metropolitan areas in Houston, TX; Denver, CO; Kansas City, MO/Lawrence, KS; Cincinnati, OH; and Washington, DC.ResultsThis pilot enabled us to evaluate the instrument itself along with the digital tool used to gather data and the process of training observers. These initial results suggest that the MMI-EC holds promise for reliably measuring Montessori practices.DiscussionThis study represents a first step in the development of an efficient, psychometrically sound assessment of Montessori fidelity for use in future research and evaluation. We offer recommendations for modifications and improvements for future iterations.